PENERAPAN TEKNOLOGI AUGMENTATIF ALTERNATIVE COMMUNICATION/AAC PADA DISABILITAS NETRA GANDA: TANTANGAN KETERLIBATAN SAUDARA KANDUNG - Hastin Trustisari; Mahatir Muhammad (Social Welfare Study Program, 2023)
Abstract. This study aims to provide an overview of the implementation of augmentative alternative communication (AAC) technology to support communication skills for multiple disability with visual impairment in the family. A qualitative descriptive approach was used to describe the involvement of adult siblings in the daily activities of individuals with multiple disability with visual impairment using AAC technology at home. The researcher conducted a literature review, in-depth interviews, and observations with four adult siblings, consisting of two siblings living in families with visually impaired parents and two other siblings in non-disabled families. The results of this study showed that there were differences in the roles played by adult siblings in disabled and non-disabled families in the implementation of AAC technology at home. This study suggests that the involvement of adult siblings is influenced by role allocation, family-school connections, parental limitations, parental roles and autonomy, and the presence of caregivers at home. The lack of school programs designed to prepare families to assist students in applying AAC technology at home has led to inconsistencies in the use of communication aids. The implications of this study suggest the possibility of further research to encourage collaborative programs between schools and parents, including the role of social workers in schools to promote the involvement of family members in improving communication skills for individuals with multiple disability with visual impairment.Top of Form Keywords: Commnucation technology, AAC, alternative communication, multiple disabilities, sibling involvement. Abstrak. Penelitian ini bertujuan memberikan gambaran penerapan teknologi augmentative alternative communication/AAC untuk mendukung keterampilan komunikasi bagi penyandang disabilitas netra ganda di keluarga. Pendekatan deskriptif kualitatif digunakan untuk menggambarkan keterlibatan saudara kandung dewasa pada aktivitas keseharian disabilitas netra ganda menggunakan teknologi AAC di rumah. Peneliti melakukan studi literatur, wawancara mendalam dan observasi pada 4 sibling dewasa yang terdiri dari 2 sibling di keluarga dengan orang tua tunanetra dan 2 sibling lainnya di keluarga non-disabilitas. Hasil penelitian ini menunjukkan bahwa terdapat perbedaan antara peran yang ditunjukkan sibling dewasa pada keluarga disabilitas dan nondisabilitas pada penerapan teknologi AAC di keluarga. Penelitian ini menegaskan bahwa keterlibatan sibling dewasa dipengaruhi oleh pembagian peran, keterhubungan keluarga dengan sekolah, keterbatasan orang tua, peran dan otonomi orang tua, serta keberadaan pengasuh di rumah. Minimnya program sekolah yang direncanakan untuk mempersiapkan keluarga mendampingi siswa dalam menerapkan teknologi AAC di rumah, ternyata memicu adanya ketidakkonsistenan dalam penggunaan alat bantu komunikasi. Penelitian ini mengharuskan penelitian lanjutan untuk mendorong program kolaborasi antara sekolah dan orang tua termasuk peran pekerja sosial di sekolah untuk mendorong keterlibatan anggota keluarga dalam peningkatan keterampilan komunikasi disabilitas netra ganda. Kata Kunci: Teknologi komunikasi, AAC, komunikasi alternative, disabilitas ganda, keterlibatan sibling.